Effect of thermomechanical treatment on the microstructure evolution and mechanical properties of lightweight Ti65(AlCrNb)35 medium-entropy alloy. (April 2022) - Liao, Y.C.; Chen, P.S.; Tsai, P.H.; Jang, J.S.C.; Hsieh, K.C.; Chang, H.W.; Chen, C.Y.; Huang, J.C.; Wu, H.J.; Lo, Y.C.; Huang, C.W.; Tsao, I.Y.
Abstract: Lightweight Ti65 (AlCrNb)35 medium-entropy alloy (Ti-65) ingots were produced through arc melting and drop casting in a water-cooled copper mold. These alloy ingots were then treated through a sequence of homogenization, hot rolling, cold rolling, and recrystallization. The effect of this thermomechanical treatment (TMT) on their microstructures and mechanical properties was investigated through X-ray diffraction (XRD), electron backscatter diffraction analysis through scanning electron microscopy, and mechanical testing. The XRD results demonstrated that the Ti-65 alloy maintained a body-centered cubic structure after 50% hot rolling, 70% cold rolling, and recrystallization at 900 °C, 1000 °C, and 1100 °C, respectively. The fully recrystallized sample had an 80% smaller grain size than the as-cast sample. The cold-rolled Ti-65 alloy specimen exhibited a high tensile strength of 1620 MPa. In comparison with the tensile strength of the as-cast Ti-65 sample (1100 MPa), that of the Ti-65 alloy following annealing and subsequent partial recrystallization was significantly increased (1380 MPa). This tensile strength enhancement is attributable to its heterostructure composition of deformed bands and smaller recrystallized grains. This study demonstrated that an effective strength–ductility synergy of the Ti-65 alloy can be achieved through various TMTs. Highlights: Thermomechanical treatment was employed to improve mechanical properties of novel lightweight Ti-65 medium-entropy alloys. The recrystallized Ti-65 medium-entropy alloys composed of fine grains can be obtained via the rapid annealing treatment. The partial-recrystallized medium-entropy alloy by rapid annealing treatment presents high strength with excellent ductility.